The creation of a temperature-regulated greenhouse model for crop cultivation in Northeastern Thailand - Sakkarin Wangkahart; Chaiyan Junsiri; Aphichat Srichat; Kittipong Laloon; Kaweepong Hongtong; Phaiboon Boupha; Somporn Katekaew; Sahassawas Poojeera (Ain Shams Engineering Journal, 2025)
This study investigated optimal greenhouse cooling configurations for extreme tropical climates using CFD modeling, focusing on Northeastern Thailand where temperatures reach 43.6 °C. The key finding revealed that a 15° air inlet angle combined with three bottom-positioned exhaust fans achieved the most effective cooling, reducing greenhouse temperature to 35.72 °C − a critical 7.88 °C reduction from ambient conditions. This configuration outperformed 30° and 45° inlet angles, which maintained higher temperatures of 36.55 °C and 36.98 °C respectively (p < 0.05). The superior performance of the 15° angle resulted from its unique spiral airflow pattern that enhanced heat transfer efficiency across plant cultivation areas. CFD simulations of 27 different ventilation configurations demonstrated that bottom-positioned exhaust fans consistently outperformed middle and top positions. Model validation showed excellent agreement with experimental data (RMSE = 2.21 °C, MAE = 0.53 °C). These findings provide a practical solution for tropical greenhouse design, offering a cost-effective approach to maintain temperatures within the optimal 25–35 °C range for crop production in regions experiencing extreme heat. The research addresses the specific needs of Thai farmers using elevated planting systems, combining temperature control with ergonomic considerations.